2021
DOI: 10.1155/2021/6661116
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinones from the Roots of Kniphofia insignis and Evaluation of Their Antimicrobial Activities

Abstract: Sequential extraction using a cold maceration method and column chromatographic separation of the roots Kniphofia insignis headed to the isolation of three anthraquinones: one monomeric anthraquinone (1) and two dimeric anthraquinones (2 and 3). It was further purified by Sephadex LH-20 and recrystallized. The structures of these compounds were established based on the spectroscopic analyses including NMR (1H-NMR and 13C-NMR and infrared) and comparison with reported literatures. In an in vitro antimicrobial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Helmantosporine ( 9 ) was isolated from the acetone fraction of Kniphofia insignis roots and tested for antibacterial and antifungal properties (Tadesse et al. 2021 ). The anti-inflammatory potential of the compound chrsophanol ( 5 ), which was obtained from the methanol crude extract fraction of Kniphofia reflexa rhizome, was also investigated (Sema et al.…”
Section: Review Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Helmantosporine ( 9 ) was isolated from the acetone fraction of Kniphofia insignis roots and tested for antibacterial and antifungal properties (Tadesse et al. 2021 ). The anti-inflammatory potential of the compound chrsophanol ( 5 ), which was obtained from the methanol crude extract fraction of Kniphofia reflexa rhizome, was also investigated (Sema et al.…”
Section: Review Methodologymentioning
confidence: 99%
“…The antibacterial and antifungal properties of asphodeline ( 10 ) derived from the acetone fraction of Kniphofia insignis roots were investigated (Tadesse et al. 2021 ). Microcarpin ( 11 ) was isolated from the rhizomes of a methanol extract of Kniphofia reflexa and tested for cytotoxicity on the LLC-MK2 Monkey Kidney Epithelial cell line using the MTT assay with Gleevec (Imatinib) as a positive control.…”
Section: Review Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…6 Because of the use of Kniphofia reflexa Hutchinson ex Codd. Asphodelaceae in the treatment of relapsing fevers, supported by literature data on the antiplasmodial activities within classes of natural products like terpenes, [7][8][9][10] flavonoids, [11][12][13] alkaloids, [14][15][16][17] quassinoids, 7,18 xanthones, [19][20][21][22] quinones, and anthraquinones, [23][24][25][26][27][28][29] a needed study of this plant was conducted considering its unique endemic nature, coupled to its classification. To the best of our knowledge, no study is reported on the antiplasmodial and antimalarial potential of chemical constituents of K reflexa.…”
Section: Introductionmentioning
confidence: 99%